Silent Fertility Pressure, Psychosomatic Infertility, and Anxiety Disorders in Arranged First Marriages - Menna Allah Hamdy Ahmed; Bakari Khatib Faki (PT. Riset Press International, 2026)
This study examines the underexplored psychological dimensions of fertility expectations within arranged first marriages. While fertility is widely regarded as a central indicator of marital success in many societies, limited attention has been given to its psychosocial consequences. This research investigates the longitudinal relationship between fertility-related social pressure, anxiety disorders, and psychosomatic infertility among women and men in Egypt and Zanzibar. Grounded in the biopsychosocial framework, Social Exchange Theory, and Symbolic Interactionism, the study employs a qualitative, comparative, and longitudinal secondary data approach, drawing on peer-reviewed literature, clinical reports, and demographic data. Findings reveal that fertility pressure is normalized, gendered, and cumulative, contributing to chronic anxiety that may manifest biologically as psychosomatic infertility, particularly among women. The study reconceptualizes infertility as not solely a biomedical condition but as a socially and psychologically mediated phenomenon. It highlights the need for interdisciplinary, culturally sensitive reproductive and mental health interventions that address both biological and psychosocial dimensions of infertility.